The Effect of Transaction Size on Off-the-Run Treasury Prices - Babbel, David F.; Merrill, Craig B.; Meyer, Mark F.; de Villiers, Meiring (Journal of Financial and Quantitative Analysis, 2004)
Abstract This paper examines intra-day trading data from the inter-dealer broker market for U.S. Treasury securities and measures the degree of price pressure in the off-the-run Treasury market. As is well known, securities that would appear to be very close substitutes, i.e., on-the-run and off-the-run Treasury bonds, behave as if there is some degree of market segmentation. This is the first systematic study of the off-the-run Treasury note and bond market focused entirely on a price pressure effect using intra-day data. The paper analyzes price pressure through matched pairs of securities that differ only in liquidity.